Design and simulation of an analog beamforming phased array antenna - Mohamed Elhefnawy (Institute of Advanced Engineering and Science, 2020)
In this paper, a phased array antenna is designed and simulated. The antenna array consists of four circularly polarized slotted waveguide elements. The antenna array is simulated using CST MWS. The simulation results for the proposed antenna array at different values of progressive phase shift demonstrate that the S‒parameters for all four ports are less than ‒10 dB over at least 2% bandwidth, the simulated maximum gain is 13.95 dB, the simulated beamwidth can be 19˚ or narrower based on the value of the progressive phase shift. , the range of frequencies over which the simulated Axial Ratio (AR) is below 3 dB is not fixed and varied according to the selected progressive phase shift. The proposed four-element RF front-end is simulated using Advanced Design System (ADS) at operating frequency of 9.6 GHz. The obtained simulation results by ADS indicate the feasibility of implementing the proposed RF-front end for feeding the antenna array to realize analog beamforming.